Византия, болгары и народы Украины в 890 г. - Howard-Johnston, J. (Материалы по археологии, истории и этнографии Таврии, 2000)
This paper offers some observations about the context of Crimean history at the end of the ninth century. It continues the story of developments in the steppe world outlined elsewhere in this volume by Alexander Aibabin and Constantine Zuckermann.